2002
DOI: 10.1348/135910702169330
|View full text |Cite
|
Sign up to set email alerts
|

Environmental illness prevalence: A population‐based study in Nova Scotia

Abstract: OBJECTIVES: Clinic studies demonstrate that people diagnosed with environmental illness experience high levels of disability and health care utilization. Even though the controversial status of this disorder attracts attention, actual prevalence estimates and estimated impact on health care systems are unclear. To address this, we sought both a prevalence estimate and a measure of the degree of health care utilization for those reporting this diagnosis. DESIGN AND METHODS: Point prevalence, as assessed by self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…One study showed an average of 23 health care visits per year for IEI subjects [20]. McGlone et al [21] found increased health care utilisation in 24 persons reporting environmental illness, compared with 48 controls. In another study, among subjects reporting hypersensitivity to common chemicals 45% reported that they had received medical treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed an average of 23 health care visits per year for IEI subjects [20]. McGlone et al [21] found increased health care utilisation in 24 persons reporting environmental illness, compared with 48 controls. In another study, among subjects reporting hypersensitivity to common chemicals 45% reported that they had received medical treatment [22].…”
Section: Introductionmentioning
confidence: 99%